HARGA DIRI DAN KOHESIVITAS KELOMPOK TERHADAP SOCIAL LOAFING PADA MAHASISWA FBB UNTAG 1945 SEMARANG - Agata, Grace; Hariadi, Lucy; Arum Permitasari, I Rheny (Psikologi Prima, 2023)
Social loafing is an intriguing problem, especially among students, because group members frequently rely on one another without providing appropriate contributions. This study aims to examine the relationship between Self-Esteem and Group Cohesiveness on Social Loafing among students at the Faculty of Language and Culture at Seventeen August University, Semarang. Quantitative correlation is utilized to collect and analyze data on 188 students. The variable Self-Esteem (X1) has a t-value of -2,317 and a significance level of 0.019, so the null hypothesis (H1) is accepted. Thus, Self-Esteem (X1) has a negative relationship with Social Loafing (Y). In the meantime, the Group Cohesiveness (X2) variable has a t value of -3,562 and a significance level of 0.000, so H2 is also accepted. This demonstrates that Group Cohesiveness (X2) has a negative and statistically significant relationship with Social Loafing (Y). They simultaneously have an  F value of 11.243 and a significance value of 0.000. This indicates that H3 is accepted, which means that Self-Esteem (X1) and Group Cohesion (X2) simultaneously influence Social Loafing (Y).